Efektivitas Distribusi Pupuk Bersubsidi untuk Usahatani Padi Saat Pandemi Covid-19 di Kecamatan Baula Kabupaten Kolaka - Muh. Yusuf; Abdi Abdi; Muhammad Aswar Limi (Universitas Halu Oleo, 2022)
This study aims to analyze the effectiveness of the distribution of subsidized fertilizers for rice crops during the COVID-19 pandemic. The study was conducted in Baula District, Kolaka Regency from October 2021 to December 2021. The population in this study were rice farmers. Determination of the sample is done by simple random sampling technique. The number of samples selected as many as 91 respondents. Data analysis used two approaches, namely a qualitative approach and a quantitative approach by calculating the effectiveness of the distribution of subsidized fertilizers based on six precise indicators, consisting of price accuracy, quantity, time, place, type and quality accuracy. Meanwhile, to determine the effect of land area, number of seeds, fertilizer, labor and the effectiveness of fertilizer distribution on rice production, multiple non-linear regression analysis was used. The results of the study show that the distribution of subsidized fertilizers in Baula District, Kolaka Regency was not effective before the pandemic, and very ineffective during the Covid-19 pandemic. Land area, number of fertilizer, seeds, and number of labor have a positive and significant effect on lowland rice production, while the effectiveness of subsidized fertilizer distribution has a positive and insignificant effect on lowland rice production.Keywords: distribution; subsidized fertilizer; Covid-19 pandemic